1998
DOI: 10.1152/ajpcell.1998.275.1.c56
|View full text |Cite
|
Sign up to set email alerts
|

Lasp-1 is a regulated phosphoprotein within the cAMP signaling pathway in the gastric parietal cell

Abstract: Activation of the cAMP signaling pathway is correlated with increased secretory-related events in a wide variety of cell types including the gastric parietal cell. Within this pathway, as well as in other intracellular signaling pathways, protein phosphorylation serves as a major downstream regulatory mechanism. However, although agonist and cAMP-dependent activation of cAMP-dependent protein kinase (PKA) has been demonstrated, little is currently known about the downstream in vivo phosphoprotein substrates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
100
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(107 citation statements)
references
References 29 publications
7
100
0
Order By: Relevance
“…To date, more than 50 different adhesion proteins that regulate the LASP-1 in human ovarian cancer TGP Grunewald et al rate and organisation of actin polymerisation and focal adhesion turnover in protrusion have been identified. In earlier publications, overexpression of LASP-1 mRNA in metastatic lymph nodes derived from breast cancer patients, as well as the co-amplification of the gene together with HER-2/neu (c-erbB2) were demonstrated (Chew et al, 1998;Legge et al, 2005). Two additional observations underscore the importance of LASP-1 in cancer.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…To date, more than 50 different adhesion proteins that regulate the LASP-1 in human ovarian cancer TGP Grunewald et al rate and organisation of actin polymerisation and focal adhesion turnover in protrusion have been identified. In earlier publications, overexpression of LASP-1 mRNA in metastatic lymph nodes derived from breast cancer patients, as well as the co-amplification of the gene together with HER-2/neu (c-erbB2) were demonstrated (Chew et al, 1998;Legge et al, 2005). Two additional observations underscore the importance of LASP-1 in cancer.…”
Section: Discussionmentioning
confidence: 75%
“…The actin-binding domains in the core of the LASP-1 protein mediate an interaction between LASP-1 and actin at cell membrane extensions, but not along the actin stress fibres (Schreiber et al, 1998;Chew et al, 2002;Butt et al, 2003;Keicher et al 2004;Nakagawa et al, 2006). The exact cellular function of LASP-1 is still not known, but the protein has previously been reported to localise within multiple sites of dynamic actin assembly such as focal contacts, focal adhesions, lamellipodia, membrane ruffles and pseudopodia (Tomasetto et al, 1995a;Chew et al, 1998Chew et al, , 2000Chew et al, , 2002Lin et al, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The 66-kDa phosphoprotein was identified by autoradiographic comparisons with unstimulated controls. Changes in phosphorylation were quantitated using Bio Image two-dimensional gel analyzer software (19,20) or a Molecular Dynamics PhosphorImager.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with the actin-binding capacity of LASP1, immunohistochemical analysis displayed a diffuse cytoplasmic staining (Schreiber et al, 1998b). In addition, in vitro studies revealed that rabbit pp40/lasp1 is one of the few unequivocally determined downstream phosphoprotein substrates of the cAMP-dependent serine/threonine protein kinase, PKC (Chew et al, 1998(Chew et al, , 2000.…”
mentioning
confidence: 88%